THE PREDICTIVE VALUE OF THE RESULTS OF LABORATORY DIAGNOSTIC TOOL IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION COMPLICATED BY DIABETES - R. D. Kurbanov; A. G. Nikishin; M. M. Pirnazarov; M. S. Khasanov; T. A. Nurbaev; N. T. Yakubbekov; S. Ya. Abdullaeva (Евразийский Кардиологический Журнал, 2013)
Purpose of research: to study the predictive value of the results of laboratory diagnostic tool in patients with acute myocardial infarction complicated by diabetes. Materials and methods: the study group -235 patients with acute myocardial infarction and type 2 diabetes. The control group - 210 patients without diabetes. Analyzed hospital clinical outcomes, laboratory methods, changes in ECG, Ultrasound cardiography, ECG monitoring, coronary angiography. Results: in the group of diabetes was significantly more frequent cases of chronic heart failure, heart rhythm disturbances. In the group of patients with diabetes, anemia was significantly frequent than in controls (18.18% versus 44.5%), as well as elevated levels of blood leukocytes and ESR levels of C-reactive protein. ECG data and Holter's monitoring show a greater frequency of persistent myocardial ischemia. Patients with diabetes and distal damage of coronary vessels (31.4% vs. 9.1% P = 0.05) was significantly higher compared with controls. Conclusion: the prognosis of patients with diabetes mellitus is caused by an active inflammatory process, the greater frequency of anemia, postinfarction ischemia, a greater degree of coronary lesions, especially the distal parts.